Correlation of Second and Third Trimester Placental Thickness with Ultrasonographic Gestational Age - Arjumand Bano; Atif Latif; Amna Zafar; Aftab, Ayma; Rasul, Tabassum; Maryam Iqbal (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the correlation between placental thickness and ultrasonographic gestational age based on foetal biometry. Study Design: Prospective Observational Study. Place and Duration of Study: Department of Diagnostic Radiology, Combined Military Hospital, Multan, Pakistan, from Dec 2024 to Sept 2025. Methodology: The study included 60 pregnant women with accurately known last menstrual periods and singleton pregnancies. Non-probability consecutive sampling was used. Patients with irregular cycles, multiple gestations, foetal anomalies or chronic medical conditions were excluded. Transabdominal ultrasonography was performed using a 3–5 MHz curved transducer to assess foetal biometric parameters (HC, BPD, FL, AC) and placental thickness in millimetres. Measurements were recorded during three gestational ages: 22–27, 28–32 and 33–36 weeks. Spearman’s correlation coefficient was applied to assess the correlation between placental thickness and gestational age. A p-value of <0.05 was considered statistically significant. Results: The median (IQR) of maternal age was 26.00 (5.00) years, median (IQR) BMI of 25.45 (3.50) kg/m² and median (IQR) parity count of 2.00 (1.00). Placental thickness increased consistently across each trimester. Strong positive correlations were observed between placental thickness and gestational age with Speraman’s rho of 0.856, 0.907 and 0.782 for the first, second and third visits respectively (p<0.001 for all). Conclusion: Placental thickness is significantly correlated with gestational age and can be utilised as a supplementary parameter in obstetric ultrasonography to estimate foetal maturity. However, the study’s single-centre design and relatively small sample size may limit generalisability.